2014
DOI: 10.1007/s12253-014-9777-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Changes in Melanoma Patients During Ipilimumab Treatment Compared to Low-Dose Interferon Alpha Therapy—A Follow-Up Study of First Experiences

Abstract: Immuntherapies are frequently accompanied by psychological side effects. Our goals were to detect the changes of psychological factors (depression, anxiety) among melanoma patients during ipilimumab treatment. Ten ipilimumab treated melanoma patients (Group 1.) and 18 low-dose interferon-alpha treated patients (Group 2.) were compared. In our longitudinal study we measured depression (Zung Self-Rating Depression Scale) and anxiety (State-Trait Anxiety Inventory, STAI). Psychological status was tested four time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Depression increased significantly over time in 1 study of stage III patients, although there was no significant change in other studies . No studies reported a change in anxiety over time . In 1 study with a sub‐group of stages III and IV patients receiving IFN‐alpha, 14 of 31 patients were diagnosed with adjustment disorder (3 stage III, 11 stage IV) .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Depression increased significantly over time in 1 study of stage III patients, although there was no significant change in other studies . No studies reported a change in anxiety over time . In 1 study with a sub‐group of stages III and IV patients receiving IFN‐alpha, 14 of 31 patients were diagnosed with adjustment disorder (3 stage III, 11 stage IV) .…”
Section: Resultsmentioning
confidence: 93%
“…Patients participating in an RCT or clinical trial most commonly received chemotherapy (eg, dacarbazine and temozolomide) ( n = 12) or interferon‐α 2a or 2b (including pegylated) ( n = 8) in 1 or both intervention arms. Patients receiving new therapies were examined in 6 studies (5 RCTs and 1 prospective quantitative study), and these included ipilimumab, dabrafenib, trametinib, a combination of dabrafenib and trametinib, or vemurafenib, in 1 or both intervention arms. Of these, only the prospective study of patients receiving ipilimumab included a measure designed specifically to assess psychosocial outcomes, as opposed to the RCTs that assessed emotional and social function using a broader QoL measure (EORTC‐QLQ‐C30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic data, such as sex, age, home, family and financial status, and level of education were measured by a standardised background questionnaire regularly used in our institute [15]. Financial status was categorized with a single question "How well do you feel you are managing financially these days?"…”
Section: Questionnairesmentioning
confidence: 99%